Cancer liquid biopsies by Oxford Nanopore Technologies sequencing of cell-free DNA: from basic research to clinical applications - Hua-Qi Si; Peng Wang; Fei Long; Wei Zhong; Yuan-Dong Meng; Yuan Rong; Xiang-Yu Meng; Fu-Bing Wang (Molecular Cancer)
Abstract Liquid biopsies, in particular, analysis of cell-free DNA, are expected to revolutionize the current landscape of cancer diagnostics and treatment. However, the existing methods for cfDNA-based liquid biopsies for cancer have certain limitations, such as fragment interruption and GC bias, which are likely to be resolved by the emerging Oxford Nanopore Technologies (ONT), characterized by long read-length, fast read-times, high throughput, and polymerase chain reaction-free. In this review, we summarized the current literatures regarding the feasibility and applications of cfDNA-based liquid biopsies using ONT for cancer management, a possible game-changer that we believe is promising in detecting multimodal biomarkers and can be applied in a wide range of oncology utilities including early screening, diagnosis, and treatment monitoring. Graphical abstract